Belgian multicenter experience with intestinal transplantation. (December 2015) - Ceulemans, Laurens J.; Monbaliu, Diethard; De Roover, Arnaud; Detry, Olivier; Troisi, Roberto I.; Rogiers, Xavier; Reding, Raymond; Lerut, Jan P.; Ysebaert, Dirk; Chapelle, Thierry; Pirenne, Jacques
Summary: Intestinal transplantation (ITx) has evolved from an experimental procedure toward a clinical reality but remains a challenging procedure. The aim of this survey was to analyze the multicenter Belgian ITx experience. From 1999 to 2014, 24 ITx in 23 patients were performed in Belgium, divided over five centers. Median recipient age was 38 years (8 months–57 years); male/female ratio was 13/10; six were children; and 17 adults. Intestinal failure was related to intestinal ischemia ( n = 5), volvulus ( n = 5), splanchnic thrombosis ( n = 4), Crohn ( n = 2), pseudo‐obstruction ( n = 2), microvillus inclusion ( n = 2), Churg‐Strauss ( n = 1), necrotizing enterocolitis ( n = 1), intestinal atresia ( n = 1), and chronic rejection ( n = 1). Graft type was isolated ITx ( n = 9), combined liver‐ITx ( n = 11) and multivisceralTx ( n = 4). One was a living donor‐related transplantation and five patients received simultaneously a kidney graft. Early acute rejection occurred in 8; late acute rejection in 4; and chronic rejection in 2. Two patients developed a post‐transplant lymphoproliferative disease. Nine patients have died. Among 14 survivors at last follow‐up, 11 have been transplanted for more than 1 year. None of the latter has developed renal failure, and all were nutritionally independent with a Karnofsky score > 90%. One‐/five‐year patient and graft survivals were 71.1%, 62.8%, 58.7% and 53.1%, respectively. Based on this experience, ITx has come of age in Belgium as a lifesaving and potentially quality of life restoring therapy.